A Discussion of eec's efficiency - Hartmut Berg (Intereconomics, 1971)
The economic aims mentioned in Article 2 of the EEC-Treaty may be summarised in the formula: “expansion and stability”. The author discusses in the following the effectiveness of the major strategies applied by the EEC within the framework of its integration policy, i.e. integration through competition within a Common Market; integration through a common policy of the member-states and integration through coordination of national economic policies.
Keywords: 330; Common Market